2001
DOI: 10.1007/s004410100445
|View full text |Cite
|
Sign up to set email alerts
|

Galanin-like immunoreactivity in the brain and pituitary of the "four-eyed" fish, Anableps anableps

Abstract: The distribution of galanin (GAL)-like immunoreactivity was investigated in the brain and pituitary of the "four-eyed" fish, Anableps anableps. GAL-immunoreactive (GAL-ir) perikarya were located in the area ventralis telencephali pars supracommissuralis, nucleus preopticus periventricularis, nucleus preopticus pars parvocellularis, nucleus preopticus pars magnocellularis, nucleus lateralis tuberis ventralis, nucleus lateralis tuberis lateralis, and nucleus lateralis tuberis posterior. A few scattered, GAL-ir n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 60 publications
4
20
0
Order By: Relevance
“…The immunohistochemical staining in our experiment demonstrated the presence of ir GAL in multiple structures within the eel brain. Our studies confirm the presence of immunoreactive cell bodies in the preoptic area observed by other authors in FW teleosts, trouts, goldfish and eels (Holmqvist and Ekström, '91;Anglade et al, '94;Rodriguez et al, 2003;Unniappan et al, 2004), in teleosts from brackish water Anableps anableps (Jadhao and Pinelli, 2001) and in SW teleost Solea senegalensis (Rodriguez-Gómez et al, 2000). The absence of ir cell bodies in Ob and in the telencephalon in the female eels, used in this investigation, well correlates with the absence of immunoreactivity in the same region observed in female trouts (Rodriguez et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The immunohistochemical staining in our experiment demonstrated the presence of ir GAL in multiple structures within the eel brain. Our studies confirm the presence of immunoreactive cell bodies in the preoptic area observed by other authors in FW teleosts, trouts, goldfish and eels (Holmqvist and Ekström, '91;Anglade et al, '94;Rodriguez et al, 2003;Unniappan et al, 2004), in teleosts from brackish water Anableps anableps (Jadhao and Pinelli, 2001) and in SW teleost Solea senegalensis (Rodriguez-Gómez et al, 2000). The absence of ir cell bodies in Ob and in the telencephalon in the female eels, used in this investigation, well correlates with the absence of immunoreactivity in the same region observed in female trouts (Rodriguez et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…GAL is also present in fish (Batten et al, '90;Holmqvist and Ekström, '91;Oliverau and Oliverau, '91;Rodriguez-Gómez et al, 2000;Rodriguez et al, 2003;Unniappan et al, 2004). In the brain of all studied teleosts, the major distribution of GAL-immunoreactive structures shows a similar pattern, with a neuronal population in the ventral telencephalon, the rostral preoptic area and in the ventral hypothalamus, GAL-immunoreactive fibres were also seen in several different brain areas, from the olfactory bulb (Ob) to the rhomboencephalon (Batten et al, '90;Oliverau and Oliverau, '91;Rao et al, '96;Jadhao and Meyer, 2000;Rodriguez-Gómez et al, 2000;Jadhao and Pinelli, 2001;Unniappan et al, 2004). The functional roles of a GAL-like substance in teleosts has mainly been attributed to pituitary functions (Moons et al,'89,'91;Batten et al,'90) and food intake stimulation (Unniappan et al, 2004;Volkoff et al, 2005).…”
mentioning
confidence: 79%
“…There is considerable evidence from mammals that galanin reduces nociception (Wiesenfeldhallin et al, 1992), increases food intake (Schick et al, 1993) and stress reactivity (Holmes et al, 2002), and that it plays a role in regulation of sexual behaviour, and is itself regulated by GnRH and estrogen (Gabriel, et al, 1993). Specifically, in fish, galanin is thought to play a role in regulation of food intake and is widely distributed in the brain, being localized to the olfactory bulb, telencephalon, hypothalamus, midbrain, and posterior brain (reviewed by Volkoff et al, 2005) as well as the pituitary (Jadhao and Pinelli, 2001) and peripheral tissues (Johnsson et al, 2001). Our results suggest the intriguing possibility that galanin might be up-regulated in dominant males as a response to reduced food intake and constant challenges to their social status by other individuals.…”
Section: Resultsmentioning
confidence: 99%
“…The primary structure of galanin is highly conserved, especially at its N‐terminus; the structure of which is essential for its biological activity (Habu et al ., 1994; Wang & Conlon, 1994 a ). Anti‐porcine galanin sera cross‐reacts with the galanins found in a range of non‐mammalian vertebrates (Lazar et al ., 1991; Jimenez et al ., 1994) including galanins within the central and peripheral nervous systems of several fish species (Anglade et al ., 1994; Holmgren et al ., 1994; Jimenez et al ., 1996; Power et al ., 1996; Batten et al ., 1999; Rodriguez‐Gomez et al ., 2000; Jadhao & Pinelli, 2001; Bosi et al ., 2004 a , b ).…”
Section: Introductionmentioning
confidence: 99%